2018
DOI: 10.1007/s12035-018-1210-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise During Pregnancy Prevents Cognitive Impairment Induced by Amyloid-β in Adult Offspring Rats

Abstract: Alzheimer's disease (AD) is the main aging-associated neurodegenerative disorder and is characterized by mitochondrial dysfunction, oxidative stress, synaptic failure, and cognitive decline. It has been a challenge to find disease course-modifying treatments. However, several studies demonstrated that regular physical activity and exercise are capable of promoting brain health by improving the cognitive function. Maternal lifestyle, including regular exercise during pregnancy, has also been shown to influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 95 publications
0
34
1
Order By: Relevance
“…Modifying the lifestyle during pregnancy may positively affect the developmental programming, protecting the offspring against metabolic dysfunctions (Klein et al, 2018; Mathias et al, 2014; Bambini‐Junior et al, 2014). In the present study, we aimed to assess the potential preventive effect of maternal exercise and maternal naringenin supplementation, isolated or in combination, on metabolic alterations in the offspring, at 21 days of age, induced by postnatal overnutrition induced by the litter size reduction model.…”
Section: Discussionmentioning
confidence: 99%
“…Modifying the lifestyle during pregnancy may positively affect the developmental programming, protecting the offspring against metabolic dysfunctions (Klein et al, 2018; Mathias et al, 2014; Bambini‐Junior et al, 2014). In the present study, we aimed to assess the potential preventive effect of maternal exercise and maternal naringenin supplementation, isolated or in combination, on metabolic alterations in the offspring, at 21 days of age, induced by postnatal overnutrition induced by the litter size reduction model.…”
Section: Discussionmentioning
confidence: 99%
“…well as metabolic alterations in the prefrontal cortex and hippocampus of young adult male rat offspring. 8 In the present study, we extended the investigation to cerebellum and observed that maternal exercise during pregnancy promotes adaptive response in developing fetuses through programming cerebellar neurochemistry that remains evident into young adulthood. Importantly, maternal exercise-induced programming was able to prevent some pathologic consequences of AβO peptide infusion, including rise of RS, protein carbonylation, and phosphorylation of tau protein.…”
mentioning
confidence: 67%
“…3 The phenotype shaping of the developing metabolism is established through plastic processes that enable an adaptation to environment 4 by metabolic programming, 5 which rely on epigenetic alterations that modulate gene expression and oxidative environment. 6 We and others have demonstrated that maternal exercise during pregnancy improves brain antioxidant defense system 7 and induces mitochondrial biogenesis 7,8 in 7-day-old rats, improves glucose homeostasis and insulin sensitivity in adult mice (>6 weeks old), 9 and neurogenesis in newborn rats 10 and young mice, 11 as well as increases brain-derived neurotrophic factor (BDNF) levels in the brain of young 10 and adult 12 rats. These findings highlight maternal exercise as a modulator of intrauterine environment that favors enhanced brain function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept evolved from Barker's studies on the thrifty phenotype, or Barker's hypothesis (Barker et al, 1989). Our group already showed how several different interventions may influence the offspring health when applied during pregnancy, such as Caloric Restriction (CR) (Stone et al, 2019), food restriction (FR) (Stone et al, 2016), high‐salt diet (Stocher et al, 2018), polyphenol supplementation (August et al, 2018), and swimming exercise (August et al, 2018; Klein et al, 2018, 2019; Marcelino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%